Laminate

JP2025022762APending Publication Date: 2025-02-14SK KAKEN CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024104879
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2024-01-09
Filing Date
2024-06-28
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0008】 本発明の積層体は、防火性に優れる。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide a laminate with superior fireproof performance.SOLUTION: A laminate of the present invention comprises at least two stacked heat-absorbing layers, including heat-absorbing layers formed from a binder and sodium tetraborate hydrate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate comprising at least two heat absorbing layers. [Background technology]

[0002] In general, fireproof materials are provided in building materials, vehicle materials, etc., for example, to suppress the transfer of heat from the outside and to increase the heat resistance of the materials. By providing such fireproof materials, the internal environment can be protected for a certain period of time in a high-heat environment or in the event of a fire. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 9-302804 Summary of the Invention [Problem to be solved by the invention]

[0004] As such a fireproof material, for example, inorganic materials such as gypsum boards are used in Patent Document 1. However, such materials may not provide sufficient fireproofing effect.

[0005] The present invention has been made in view of the above problems, and an object of the present invention is to provide a laminate having excellent fire retardancy. [Means for solving the problem]

[0006] As a result of intensive research into solving the above problems, the inventors discovered that a laminate having at least two heat absorption layers, including a heat absorption layer formed from a binder and sodium tetraborate hydrate, has excellent fire resistance, leading to the completion of the present invention.

[0007] That is, the present invention has the following features. 1. A laminate including a first heat absorption layer and a second heat absorption layer, 13. A laminate, wherein the first heat absorption layer and / or the second heat absorption layer is formed from a binder and sodium tetraborate hydrate. 2. A laminate including a first heat absorption layer and a second heat absorption layer, 13. A laminate comprising the first heat absorption layer and the second heat absorption layer, the first heat absorption layer and the second heat absorption layer being formed from a binder and sodium tetraborate hydrate. 3. A laminate including a first heat absorption layer and a second heat absorption layer, the first heat absorption layer is formed of a binder and sodium tetraborate hydrate; 2. A laminate, wherein the second heat absorption layer is formed from an inorganic binder and is substantially free of sodium tetraborate hydrate. 4. The laminate described in any one of 1. to 3., wherein the sodium tetraborate hydrate includes sodium tetraborate decahydrate. 5. A laminate according to any one of 1. to 3., wherein the binder comprises an organic binder. 6. The laminate according to 5, wherein the organic binder is obtained from an unsaturated polyester and an unsaturated monomer. 7. The laminate described in any one of 1. to 3., wherein the thickness of the first heat absorption layer and the second heat absorption layer is 50 mm or less, respectively. Effect of the Invention

[0008] The laminate of the present invention has excellent fire retardancy. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, an embodiment of the present invention will be described.

[0010] The laminate of the present invention includes at least a first heat absorption layer and a second heat absorption layer, and at least one of the first heat absorption layer and the second heat absorption layer is formed from a binder and sodium tetraborate hydrate. As for the other heat absorption layer, various heat absorption layers having heat absorption properties can be used.

[0011] As a preferred embodiment of the laminate of the present invention, for example, (1) A laminate in which the first heat absorption layer and the second heat absorption layer are heat absorption layers formed of a binder and sodium tetraborate hydrate; (2) A laminate in which the first heat absorption layer is a heat absorption layer formed of a binder and sodium tetraborate hydrate, and the second heat absorption layer is a heat absorption layer formed of an inorganic binder and does not substantially contain sodium tetraborate hydrate. Examples include: The heat absorbing layer formed by the binder and sodium tetraborate hydrate is a layer that exerts a heat absorbing effect by sodium tetraborate hydrate, and is hereinafter also referred to as heat absorbing layer (A). The heat absorbing layer formed by the inorganic binder and substantially free of sodium tetraborate hydrate is a layer that exerts a heat absorbing effect by the inorganic binder, and is hereinafter also referred to as heat absorbing layer (B).

[0012] [Heat absorption layer (A)] (Binding Agent) The binder may be an organic binder or an inorganic binder. From the viewpoint of weight reduction, an organic binder is preferred, and from the viewpoint of heat absorption, an inorganic binder is preferred.

[0013] (Organic Binder) Examples of the organic binder include polyether resin, polyester resin, unsaturated polyester resin, vinyl acetate resin, alkyd resin, epoxy resin, acrylic resin, acrylic silicone resin, urethane resin, phenol resin, melamine resin, polycarbonate resin, fluororesin, acrylic-vinyl acetate resin, acrylic-urethane resin, acrylic-epoxy resin, acrylic-silicone resin, silicone modified acrylic resin, ethylene-vinyl acetate resin, etc., and among them, from the viewpoint of weight reduction, it is preferable to use one obtained from polyol and isocyanate (the urethane resin obtained by reaction and hardening), or one obtained from unsaturated polyester and unsaturated monomer (the unsaturated polyester resin obtained by reaction and hardening). The urethane resin can reduce the density, so it is useful for reducing the weight of the laminate obtained, and the unsaturated polyester resin can reduce the thickness, so it is useful for reducing the weight of the laminate obtained.

[0014] (Polyol) Examples of the polyol include polyester polyol, polyether polyol, polycarbonate polyol, polylactone polyol, polybutadiene polyol, polypentadiene polyol, castor oil, castor oil-based polyol, and the like. One or more of these can be used.

[0015] Examples of the polyester polyol include aromatic polyester polyol, aliphatic polyester polyol, and aromatic / aliphatic polyester polyol.

[0016] Specifically, the aliphatic polyester polyol is a polyol having an aliphatic hydrocarbon in one molecule, and examples thereof include condensation polyester polyols obtained by reacting a saturated aliphatic polybasic acid such as succinic acid, adipic acid, azelaic acid, or sebacic acid with a polyhydric alcohol, and condensation polyester polyols obtained by reacting an unsaturated aliphatic polybasic acid such as maleic acid or fumaric acid with a polyhydric alcohol.

[0017] The aromatic polyester polyol is a polyol having an aromatic hydrocarbon in one molecule, and examples thereof include condensed polyester polyols obtained by reacting an aromatic polybasic acid such as orthophthalic acid, isophthalic acid, terephthalic acid, phthalic anhydride, etc. with a polyhydric alcohol, and phthalic acid-based polyester polyols obtained by decomposing a phthalic acid-based polyester molded product such as polyethylene terephthalate, etc. In addition, examples of the polyhydric alcohol include dihydric or higher alcohols and derivatives thereof, dihydric or higher phenols, polyols, etc.

[0018] The aromatic / aliphatic polyester polyol is a polyol having an aliphatic hydrocarbon and an aromatic hydrocarbon in one molecule, and examples thereof include condensation polyester polyols obtained by reacting an aromatic polybasic acid or an aliphatic polybasic acid with a polyhydric alcohol.

[0019] Examples of the polyether polyol include aromatic polyether polyols, phosphorus-containing polyether polyols, glycerin-based polyether polyols, and amino group-containing polyether polyols.

[0020] Examples of the aromatic polyether polyol include bisphenol A-type polyether polyols obtained by adding an alkylene oxide (e.g., ethylene oxide, propylene oxide, etc.) to bisphenol A as an initiator, and aromatic amine-based polyether polyols obtained by adding an alkylene oxide to an aromatic amine (e.g., toluenediamine, diethyltoluenediamine, 4,4'-diaminodiphenylmethane, p-phenylenediamine, o-phenylenediamine, naphthalenediamine, triethanolamine, Mannich condensation products, etc.) as an initiator.

[0021] Examples of the phosphorus-containing polyether polyol include dialkyl-N,N-bis(2-hydroxyethyl)aminomethylphosphonate, which is a diol having a phosphoric acid ester structure.

[0022] The glycerin-based polyether polyols include polyether polyols obtained by adding alkylene oxide to glycerin as an initiator.

[0023] Examples of the amino group-containing polyether polyol include those obtained by adding an alkylene oxide to a low molecular weight amine (for example, ethylenediamine, propylenediamine, butylenediamine, hexamethylenediamine, neopentyldiamine, etc.) as an initiator.

[0024] The castor oil-based polyol is a polymer derived from castor oil or castor oil fatty acid, and examples thereof include alkylene oxide adducts of castor oil or castor oil fatty acid, epoxidized products of castor oil or castor oil fatty acid, halides of castor oil or castor oil fatty acid, transesterification products of castor oil or castor oil fatty acid and polyhydric alcohol, and hydrogenated products thereof. In the present invention, castor oil-based polyols and / or castor oil are particularly preferred, and it is more preferred that they contain castor oil.

[0025] In particular, in the present invention, the polyol is preferably one containing a castor oil-based polyol and / or castor oil, and more preferably one containing castor oil.

[0026] The mixing ratio (mass ratio of solid contents) of the castor oil-based polyol to the castor oil is preferably 0:100 to 50:50, and more preferably 0:100 to 30:70.

[0027] The hydroxyl value of the polyol in the present invention is not particularly limited, but is preferably from 50 mgKOH / g to 500 mgKOH / g. The hydroxyl value is expressed as the number of milligrams of potassium hydroxide equivalent to the moles of hydroxyl groups contained in 1 g of sample, and is measured based on JIS K 1557-1:2007 Plastics - Test method for polyurethane raw material polyols - Part 1: Determination of hydroxyl value. The hydroxyl value of a polyol is the value measured for a mixture of all polyols.

[0028] (Isocyanate) The isocyanate has two or more isocyanate groups in one molecule and reacts with the polyol to form a molded product. Various isocyanates known in the polyurethane technical field can be used.

[0029] Examples of the isocyanate include aliphatic diisocyanates, alicyclic diisocyanates, aromatic diisocyanates, araliphatic diisocyanates, etc., and derivatives thereof by allophanation, biuretization, dimerization (uretidione), trimerization (isocyanurate), adductization, carbodiimide reaction, etc., mixtures thereof, and copolymers thereof with monomers copolymerizable therewith, etc. These can be used alone or in combination of two or more.

[0030] Examples of the aliphatic diisocyanate include 1,3-trimethylene diisocyanate, 1,4-tetramethylene diisocyanate, 1,3-pentamethylene diisocyanate, 1,5-pentamethylene diisocyanate, 1,6-hexamethylene diisocyanate (HMDI), 1,2-propylene diisocyanate, 1,2-butylene diisocyanate, 2,3-butylene diisocyanate, and 1,3-butylene diisocyanate. anate, 2-methyl-1,5-pentamethylene diisocyanate, 3-methyl-1,5-pentamethylene diisocyanate, 2,4,4-trimethyl-1,6-hexamethylene diisocyanate, 2,2,4-trimethyl-1,6-hexamethylene diisocyanate, 2,6-diisocyanate methyl caproate, lysine diisocyanate, dimer acid diisocyanate, and norbornene diisocyanate.

[0031] Examples of the alicyclic diisocyanate include 1,3-cyclopentane diisocyanate, 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, 1,4-bis(isocyanatomethyl)cyclohexane, isophorone diisocyanate (IPDI), norbornane diisocyanate, dicyclohexylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, and hydrogenated xylylene diisocyanate.

[0032] Examples of the aromatic diisocyanate include m-phenylene diisocyanate, p-phenylene diisocyanate, 2,4-tolylene diisocyanate (TDI), 2,6-tolylene diisocyanate (TDI), naphthylene-1,4-diisocyanate, naphthylene-1,5-diisocyanate, 4,4'-diphenyl diisocyanate, 4,4'-diphenylmethane diisocyanate (MDI), 2,4'-diphenylmethane diisocyanate, Examples of the isocyanate include 4,4'-diphenyl ether diisocyanate, 2-nitrodiphenyl-4,4'-diisocyanate, 2,2'-diphenylpropane-4,4'-diisocyanate, 3,3'-dimethyldiphenylmethane-4,4'-diisocyanate, 4,4'-diphenylpropane diisocyanate, 3,3'-dimethoxydiphenyl-4,4'-diisocyanate, dianisidine diisocyanate, and tetramethylene xylylene diisocyanate.

[0033] Examples of the aromatic aliphatic diisocyanate include 1,3-xylylene diisocyanate (XDI), 1,4-xylylene diisocyanate (XDI), ω,ω'-diisocyanate-1,4-diethylbenzene, 1,3-bis(1-isocyanate-1-methylethyl)benzene, 1,4-bis(1-isocyanate-1-methylethyl)benzene, and 1,3-bis(α,α-dimethylisocyanate methyl)benzene.

[0034] In the present invention, it is particularly preferable to use aliphatic diisocyanates such as HMDI and its derivatives, aromatic diisocyanates such as MDI and its derivatives, etc. Furthermore, in the present invention, it is preferable to use trimerized (isocyanurated) aliphatic diisocyanates or aromatic diisocyanates, and in particular, it is preferable to use trimerized (isocyanurated) aliphatic diisocyanates in the present invention.

[0035] In the present invention, the isocyanate index is preferably from 100 to 500 (more preferably from 105 to 400, and even more preferably from 110 to 300). By mixing the polyol and the isocyanate in such a range, a urethane resin having excellent heat resistance and a heat absorbing layer (A) using the urethane resin can be obtained. The isocyanate index is expressed as 100 times the value obtained by dividing the number of equivalents of isocyanate groups in an isocyanate by the total number of equivalents of active hydrogen in an active hydrogen-containing component (polyol). In addition, the water liberated from the hydrate of sodium tetraborate, which will be described later, is not counted as an active hydrogen-containing component used in the above isocyanate index.

[0036] (Unsaturated polyester) The unsaturated polyester may be, for example, one produced by an esterification reaction between a polyhydric alcohol and a polybasic acid.

[0037] Examples of the polyhydric alcohol include alkylene glycols such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, and neopentyl glycol, trimethylolethane, trimethylolpropane, glycerin, pentaerythritol, 1,6-hexanediol, ester glycol, 1,4-cyclohexanedimethanol, and 1,3-butanediol, and these can be used alone or in combination of two or more.

[0038] Examples of the polybasic acid include unsaturated polybasic acids such as maleic acid, maleic anhydride, fumaric acid, itaconic acid, itaconic anhydride, and citraconic acid. Phthalic acid (orthophthalic acid), isophthalic acid, terephthalic acid, phthalic anhydride, tetrahydrophthalic acid, tetrahydrophthalic anhydride, hexahydrophthalic acid, hexahydrophthalic anhydride, cyclohexanedicarboxylic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, azelaic acid, sebacic acid, trimellitic acid, and pyromellitic acid can also be used in combination, and one or more of these can be used.

[0039] (Unsaturated Monomer) Examples of the unsaturated monomer include (meth)acrylic acid ester monomers such as methyl (meth)acrylate, and aromatic monomers such as styrene, methylstyrene, and divinylbenzene, and one or more of these can be used.

[0040] In the present invention, the mixing ratio of the unsaturated polyester and the unsaturated monomer is preferably 10 parts by mass or more and 200 parts by mass or less, more preferably 20 parts by mass or more and 180 parts by mass or less, relative to 100 parts by mass of the unsaturated polyester. By mixing the unsaturated polyester and the unsaturated monomer in such a range and, if necessary, adding an initiator, etc., it is possible to obtain an unsaturated polyester resin having excellent heat resistance and a heat absorbing layer (A) using the unsaturated polyester resin.

[0041] (Inorganic binder) Examples of the inorganic binder include hydraulic inorganic binders, and among them, hydraulic inorganic binders are preferred from the viewpoint of heat absorption.

[0042] Examples of the hydraulic inorganic binder include portland cement, alumina cement, ultra rapid hardening cement, expansion cement, acidic phosphate cement, silica cement, lime mixed cement, blast furnace cement, fly ash cement, Keene's cement, magnesia cement, dolomite, calcium silicate, hydraulic lime, gypsum, etc., and one or more of these can be used.

[0043] (Sodium tetraborate hydrate) The sodium tetraborate hydrate is a component that imparts endothermic properties. As the sodium tetraborate hydrate, from the viewpoint of endothermic properties, sodium tetraborate pentahydrate and sodium tetraborate decahydrate are more preferable, and among them, sodium tetraborate decahydrate is particularly preferable from the viewpoint of excellent endothermic properties, since a large amount of hydration water is liberated from the hydrate and the temperature at which it is liberated is relatively low (about 60° C.).

[0044] The sodium tetraborate pentahydrate is a substance that releases water of hydration at temperatures from about 100 to 150°C. The sodium tetraborate decahydrate is a substance that releases water of hydration at temperatures from about 60°C.

[0045] The content of the sodium tetraborate hydrate is preferably 5% by mass or more and 90% by mass or less (further, 10% by mass or more and 80% by mass or less, furthermore, 20% by mass or more and 70% by mass or less) of the entire heat-absorbing layer (A). Within such a range, a heat-absorbing layer (A) having sufficient heat absorption and light weight can be obtained.

[0046] The amount of the sodium tetraborate hydrate mixed is preferably 5 parts by mass or more and 2000 parts by mass or less (more preferably 10 parts by mass or more and 1800 parts by mass or less, and even more preferably 20 parts by mass or more and 1500 parts by mass or less) per 100 parts by mass of the binder.

[0047] When the binder is a urethane resin, it is particularly preferable that the amount of the sodium tetraborate hydrate mixed is 30 parts by mass or more and 2000 parts by mass or less (more preferably 50 parts by mass or more and 1800 parts by mass or less, and even more preferably 100 parts by mass or more and 1500 parts by mass or less) per 100 parts by mass of the polyol. In addition, when the binder is a urethane resin, the sodium tetraborate hydrate is a component that can contribute to weight reduction by mixing the polyol and the isocyanate, and the water liberated from the sodium tetraborate hydrate reacts with the isocyanate to generate carbon dioxide and foam, and is also a component that contributes to the lightness of the heat absorption layer (A).

[0048] When the binder is an unsaturated polyester resin, it is particularly preferable that the amount of the sodium tetraborate hydrate mixed is 40 parts by mass or more and 2000 parts by mass or less (more preferably 80 parts by mass or more and 1800 parts by mass or less, and even more preferably 120 parts by mass or more and 1500 parts by mass or less) per 100 parts by mass of the unsaturated polyester.

[0049] The heat absorbing layer (A) can be obtained by mixing other additives in addition to the above-mentioned components. Examples of the other additives include fillers, flame retardants, foaming agents, foam stabilizers, viscosity adjusters, hardening accelerators, initiators, metal hydrates, colorants, dyes, film-forming assistants, leveling agents, wetting agents, plasticizers, antifreeze agents, pH adjusters, preservatives, antifungal agents, anti-algae agents, antibacterial agents, dispersants, surfactants, adsorbents, fibers, carbonizing agents, and solvents.

[0050] Examples of the filler include heavy calcium carbonate, kaolin, diatomaceous earth, white carbon, clay, talc, barite powder, precipitated barium sulfate, barium carbonate, silica sand, vermiculite, ceramic beads, glass beads, silica gel, perlite, expanded vermiculite, pumice, vermiculite, crushed ALC, hollow ceramic beads, hollow glass beads, shirasu balloons, charcoal, bamboo charcoal, seed shell charcoal, smoked seed shell charcoal, styrene resin foam, ethylene vinyl acetate resin foam, polyvinyl chloride resin foam, and the like. One or more of these may be used.

[0051] The amount of the filler to be mixed may be from 10 parts by mass to 500 parts by mass (or from 20 parts by mass to 400 parts by mass) relative to 100 parts by mass of the binder. In particular, when the binder is a urethane resin, the amount of the filler to be mixed may be 30 parts by mass or more and 500 parts by mass or less (even more preferably 50 parts by mass or more and 400 parts by mass or less) relative to 100 parts by mass of the polyol.

[0052] In particular, when the binder is an unsaturated polyester resin, the amount of the filler to be mixed may be 40 parts by mass or more and 500 parts by mass or less (even 80 parts by mass or more and 400 parts by mass or less) per 100 parts by mass of the unsaturated polyester.

[0053] In particular, in the present invention, the filler has a bulk density of 0.01 g / cm 3 More than 1g / cm 3 A lightweight filler having a mass of less than 10 ... Furthermore, in the present invention, one or more non-combustible lightweight fillers selected from perlite, expanded vermiculite, pumice, vermiculite, crushed ALC, ceramic hollow beads, hollow glass beads, charcoal, bamboo charcoal, seed shell charcoal, and smoked seed shell charcoal can be used.

[0054] The amount of the lightweight filler to be mixed may be 300 parts by mass or less (even more preferably 1 part by mass or more and 250 parts by mass or less) relative to 100 parts by mass of the binder. The amount of the lightweight filler in this range is advantageous in terms of lightness and strength. In addition, when the lightweight filler is a non-flammable lightweight filler, it is also advantageous in terms of heat resistance.

[0055] In particular, when the binder is a urethane resin, the amount of the lightweight filler to be mixed may be 300 parts by mass or less (even more preferably 1 part by mass or more and 250 parts by mass or less) relative to 100 parts by mass of the polyol. The lightweight filler in such a range is advantageous in terms of lightness and strength. In addition, when the lightweight filler is a non-flammable lightweight filler, it is also advantageous in terms of heat resistance.

[0056] In the case where the binder is an unsaturated polyester resin, the amount of the lightweight filler to be mixed may be 300 parts by mass or less (even more preferably 1 part by mass or more and 250 parts by mass or less) relative to 100 parts by mass of the unsaturated polyester. The lightweight filler in such a range is advantageous in terms of lightness and strength. In addition, when the lightweight filler is a non-flammable lightweight filler, it is also advantageous in terms of heat resistance.

[0057] The bulk density of the filler is a value measured by supplying the filler to a cylindrical container and applying up and down vibration (tapping vibration) to the filler in the container until the bulk change of the filler in the container ends.

[0058] The average particle size of the filler is not particularly limited, but may be from 50 μm to 1000 μm. The average particle size of the filler can be measured by a laser diffraction particle size distribution measuring device.

[0059] Examples of the flame retardant include phosphorus-based flame retardants, halogen-based flame retardants, boron-based flame retardants, metal hydroxide-based flame retardants, nitrogen-based flame retardants, and silicon-based flame retardants, and one or more of these can be used.

[0060] Examples of the phosphorus-based flame retardant include phosphate ester compounds, phosphate compounds, polyphosphate compounds, phosphite compounds, phosphonate compounds, phosphonite compounds, phosphinate compounds, phosphinate compounds, red phosphorus, phosphorus trichloride, and phosphorus pentachloride.

[0061] Specific examples of the phosphoric acid ester compound include trimethyl phosphate, triethyl phosphate, tributyl phosphate, trioctyl phosphate, triphenyl phosphate, trisnonylphenyl phosphate, tributoxyethyl phosphate, tricresyl phosphate, cresyl phenyl phosphate, cresyl diphenyl phosphate, octyl diphenyl phosphate, trixylenyl phosphate, diisopropyl phenyl phosphate, tris(2-ethylhexyl)phosphate, resorcinol bisdiphenyl phosphate, bisphenol A bis(diphenyl phosphate), resorcinol bisdixylenyl phosphate, tris(chloroethyl)phosphate, tris(chloropropyl)phosphate, tris(dichloropropyl)phosphate, bis(2, 3-dibromopropyl)-2,3-dichloropropyl phosphate, tris(2,3-dibromopropyl)phosphate, bis(chloropropyl)monoctyl phosphate, hydroquinonyl diphenyl phosphate, phenyl nonyl phenyl hydroquinonyl phosphate, phenyl dinonyl phenyl phosphate, diphenyl-4-hydroxy-2,3,5,6-tetrabromobenzyl phosphonate, dimethyl-4-hydroxy-3,5-dibromobenzyl phosphonate, diphenyl-4-hydroxy-3,5-dibromobenzyl phosphonate, trialkyl polyphosphate, resorcinol polyphenyl phosphate, bisphenol A polycresyl phosphate, resorcinol poly(di-2,6-xylyl)phosphate, hydroquinone poly(2,6-xylyl)phosphate, and the like.

[0062] Examples of the phosphate compound include aluminum phosphate, sodium phosphate, potassium phosphate, calcium phosphate, zinc phosphate, ammonium phosphate, aluminum phosphite, sodium phosphite, potassium phosphite, calcium phosphite, zinc phosphite, ammonium phosphite, aluminum hypophosphite, sodium hypophosphite, potassium hypophosphite, calcium hypophosphite, zinc hypophosphite, ammonium hypophosphite, aluminum metaphosphate, sodium metaphosphate, potassium metaphosphate, calcium metaphosphate, and zinc metaphosphate.

[0063] Examples of the polyphosphate compound include ammonium polyphosphate, ammonium amide polyphosphate, melamine polyphosphate, piperazine polyphosphate, melem polyphosphate, melam polyphosphate, melon polyphosphate, and aluminum polyphosphate.

[0064] Examples of the phosphonate compound include methylphosphonic acid, dimethyl methylphosphonate, diethyl methylphosphonate, ethylphosphonic acid, propylphosphonic acid, butylphosphonic acid, 2-methylpropylphosphonic acid, t-butylphosphonic acid, 2,3-dimethyl-butylphosphonic acid, octylphosphonic acid, phenylphosphonic acid, and dioctyl phenylphosphonate.

[0065] Examples of the phosphinic acid salt compound include dimethylphosphinic acid, methylethylphosphinic acid, methylpropylphosphinic acid, diethylphosphinic acid, dioctylphosphinic acid, phenylphosphinic acid, diethylphenylphosphinic acid, diphenylphosphinic acid, and bis(4-methoxyphenyl)phosphinic acid.

[0066] The halogen-based flame retardants include, for example, those containing fluorine, chlorine, bromine, iodine, and antimony, and examples thereof include halogen oxides, halogenated phosphazenes, halogenated alkanes, halogenated indanes, halogenated phosphates, and halogenated polystyrenes.

[0067] Examples of the boron-based flame retardants include boron oxide, boric acid, lithium borate, sodium borate (excluding sodium tetraborate hydrate), potassium borate, cesium borate, magnesium borate, calcium borate, barium borate, zirconium borate, zinc borate, aluminum borate, and ammonium borate.

[0068] Examples of the metal hydroxide-based flame retardant include aluminum hydroxide, magnesium hydroxide, calcium hydroxide, iron hydroxide, nickel hydroxide, zirconium hydroxide, zinc hydroxide, titanium hydroxide, copper hydroxide, tin hydroxide, and vanadium hydroxide.

[0069] The amount of the flame retardant mixed is preferably 5 parts by mass or more and 1000 parts by mass or less (more preferably 10 parts by mass or more and 500 parts by mass or less, even more preferably 15 parts by mass or more and 200 parts by mass or less, still more preferably 20 parts by mass or more and 100 parts by mass or less, and most preferably 25 parts by mass or more and 80 parts by mass or less) relative to 100 parts by mass of the binder. By setting the amount of the flame retardant in such a range, it is possible to improve dispersibility and to achieve both heat resistance and light weight.

[0070] In the case where the binder is a urethane resin, the amount of the flame retardant mixed is preferably 10 parts by mass or more and 1000 parts by mass or less (more preferably 15 parts by mass or more and 500 parts by mass or less, even more preferably 20 parts by mass or more and 200 parts by mass or less, even more preferably 25 parts by mass or more and 100 parts by mass or less, and most preferably 30 parts by mass or more and 80 parts by mass or less) relative to 100 parts by mass of the polyol. By setting the amount of the flame retardant in such a range, it is possible to improve dispersibility and to achieve both heat resistance and light weight. In particular, it is preferable to use, as the polyol, a castor oil-based polyol and / or castor oil (more preferably castor oil) in the above-mentioned mixing ratio.

[0071] In the case where the binder is an unsaturated polyester resin, the amount of the flame retardant mixed is preferably 10 parts by mass or more and 1000 parts by mass or less (more preferably 15 parts by mass or more and 500 parts by mass or less, even more preferably 20 parts by mass or more and 200 parts by mass or less, even more preferably 25 parts by mass or more and 100 parts by mass or less, and most preferably 30 parts by mass or more and 80 parts by mass or less) relative to 100 parts by mass of the unsaturated polyester. By setting the amount of the flame retardant in such a range, it is possible to improve dispersibility and to achieve both heat resistance and light weight. In particular, it is preferable to use, as the unsaturated polyester, one produced by an esterification reaction between a polyhydric alcohol selected from ethylene glycol and propylene glycol and a polybasic acid selected from maleic acid, maleic anhydride, fumaric acid, and isophthalic acid, and to use, as the unsaturated monomer, a (meth)acrylic acid ester monomer and / or an aromatic monomer in the above-mentioned mixing ratio.

[0072] In the present invention, it is preferable to use the flame retardant and the sodium tetraborate hydrate in combination, which can improve the heat resistance, and in particular, by using a liquid flame retardant in combination, the dispersion stability of the sodium tetraborate hydrate and the viscosity of the composition can be controlled, and a heat absorbing layer having excellent heat resistance and light weight can be obtained.

[0073] The foaming agent is not particularly limited, but examples thereof include hydrofluoroolefins, hydrochlorofluoroolefins, water, liquefied carbon dioxide gas, etc., and one or more of these can be used.

[0074] Examples of the hydrofluoroolefin (HFO) include pentafluoropropenes such as 1,2,3,3,3-pentafluoropropene (HFO1225ye), tetrafluoropropenes such as 1,3,3,3-tetrafluoropropene (HFO1234ze), 2,3,3,3-tetrafluoropropene (HFO1234yf), and 1,2,3,3-tetrafluoropropene (HFO1234ye), and 3,3,3-trifluoropropene. Examples of suitable fluoropropenes include trifluoropropene (HFO1243zf), tetrafluorobutene (HFO1345), pentafluorobutene (HFO1354), hexafluorobutene (HFO1336), heptafluorobutene (HFO1327), heptafluoropentene (HFO1447), octafluoropentene (HFO1438), nonafluoropentene (HFO1429), and isomers thereof (cis isomer, trans isomer).

[0075] Examples of the hydrochlorofluoroolefin (HCFO) include 1-chloro-3,3,3-trifluoropropene (HCFO-1233zd), 2-chloro-3,3,3-trifluoropropene (HCFO-1233xf), dichlorotrifluoropropene (HCFO1223), and isomers thereof (cis isomer, trans isomer).

[0076] The blowing agent in the present invention is preferably one or more selected from hydrofluoroolefins, hydrochlorofluoroolefins, and water. For example, each blowing agent can be used in combination, such as hydrofluoroolefin and water, hydrochlorofluoroolefin and water, or hydrofluoroolefin, hydrochlorofluoroolefin and water.

[0077] In particular, when the binder is a urethane resin, the amount of the foaming agent mixed is preferably 200 parts by mass or less, more preferably 20 parts by mass or more and 180 parts by mass or less, and even more preferably 30 parts by mass or more and 150 parts by mass or less, relative to 100 parts by mass of the polyol.

[0078] Examples of the foam stabilizer include silicone-based foam stabilizers such as polyether-modified silicone compounds, fluorine-containing compound-based foam stabilizers, etc. These may be used alone or in combination of two or more.

[0079] Examples of the polyether-modified silicone compound include graft copolymers of polydimethylsiloxane and polyoxyethylene glycol or polyoxyethylene-propylene glycol.

[0080] In particular, when the binder is a urethane resin, the amount of the foam stabilizer mixed is preferably 40 parts by mass or less, and more preferably 0.5 parts by mass or more and 30 parts by mass or less, relative to 100 parts by mass of the polyol.

[0081] Examples of the viscosity regulator include layered clay minerals such as smectite and vermiculite, amide wax, hydrophobic cellulose such as ethyl cellulose and cellulose nitrate, and polyolefins such as polyethylene and polypropylene, and one or more of these can be used. In particular, in the present invention, it is preferable to use layered clay minerals, and it is particularly preferable to use layered clay minerals that have been organically treated with long-chain alkyl ammonium ions or the like (organic smectites (organic montmorillonite, organic bentonite, etc.), organic vermiculite, etc.).

[0082] In particular, when the binder is a urethane resin, the mixing amount of the viscosity modifier is preferably 60 parts by mass or less, and more preferably 1.0 part by mass or more and 40 parts by mass or less, relative to 100 parts by mass of the polyol.

[0083] In particular, when the binder is an unsaturated polyester resin, the amount of the viscosity modifier mixed is preferably 50 parts by mass or less, and more preferably 0.1 to 30 parts by mass, per 100 parts by mass of the unsaturated polyester.

[0084] Examples of the curing accelerator include amines such as triethylamine, triethylenediamine, triethylamine, tetramethylbutanediamine, dimethylaminoethanol, dimer diamine, and dimer acid polyamide amine; tin carboxylates such as dibutyltin dilaurate, dibutyltin diacetate, and tin octoate; metal carboxylates such as iron naphthenate, cobalt naphthenate, manganese naphthenate, zinc naphthenate, iron octylate, cobalt octylate, manganese octylate, and zinc octylate; carboxylates such as dibutyltin thiocarboxylate, dioctyltin thiocarboxylate, tributylmethylammonium acetate, and trioctylmethylammonium acetate; and aluminum compounds such as aluminum trisacetylacetate. One or more of these may be used.

[0085] In particular, when the binder is a urethane resin, the amount of the curing accelerator mixed is preferably 0.05 to 40 parts by mass, and more preferably 0.1 to 30 parts by mass, based on 100 parts by mass of the polyol.

[0086] Examples of the initiator include organic peroxides such as hydroperoxides, dialkyl peroxides, diacyl peroxides, ketone peroxides, peroxy esters, peroxy ketals, and peroxy dicarbonates; and azo compounds such as azobisisobutyronitrile, azobiscarbonamide, and 2-phenylazo-2,4-dimethyl-4-methoxyvaleronitrile. One or more of these can be used.

[0087] In particular, when the binder is an unsaturated polyester resin, the amount of the initiator mixed is preferably 0.05 parts by mass or more and 10 parts by mass or less, and more preferably 0.1 parts by mass or more and 80 parts by mass or less, relative to 100 parts by mass of the unsaturated monomer.

[0088] The heat absorbing layer (A) may contain other metal hydrates in addition to the sodium tetraborate hydrate. Examples of such metal hydrates include sulfates such as ammonium aluminum sulfate dodecahydrate, sodium aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, magnesium sulfate dodecahydrate, sodium sulfate dodecahydrate, nickel sulfate dodecahydrate, zinc sulfate dodecahydrate, beryllium sulfate dodecahydrate, zirconium sulfate dodecahydrate, and other sulfates; sulfites such as zinc sulfite dihydrate and sodium sulfite dodecahydrate; aluminum phosphate dihydrate, cobalt phosphate octahydrate, magnesium phosphate octahydrate, and other sulfates; phosphates such as sium octahydrate, magnesium ammonium phosphate hexahydrate, magnesium hydrogen phosphate trihydrate, magnesium hydrogen phosphate heptahydrate, zinc phosphate tetrahydrate, and zinc dihydrogen phosphate dihydrate; nitrates such as aluminum nitrate nonahydrate, zinc nitrate hexahydrate, calcium nitrate tetrahydrate, cobalt nitrate hexahydrate, bismuth nitrate pentahydrate, zirconium nitrate pentahydrate, cerium nitrate hexahydrate, iron nitrate hexahydrate, iron nitrate nonahydrate, nickel nitrate hexahydrate, and magnesium nitrate hexahydrate; acetates such as zinc acetate dihydrate and cobalt acetate tetrahydrate; chloride salts such as cobalt chloride hexahydrate and iron chloride tetrahydrate; and borates such as disodium octaborate tetrahydrate and zinc borate 3.5-hydrate.

[0089] The heat-absorbing layer (A) can be prepared by mixing the polyol, the isocyanate, and the sodium tetraborate hydrate, adding and mixing other additives as necessary, and curing the mixture to obtain the heat-absorbing layer (A) containing the urethane resin and the sodium tetraborate hydrate. In particular, a first liquid (first component) containing the polyol, the sodium tetraborate hydrate, and, if necessary, other additives is prepared, and a second liquid (second component) containing an isocyanate is prepared, and the first liquid and the second liquid are mixed and reacted to obtain the heat absorbing layer (A). The sodium tetraborate hydrate and other additives may be mixed only with the first component, or may be mixed with the second component if necessary. In such a case, it is particularly preferable to mix and react at a temperature of 10° C. or higher and 70° C. or lower (more preferably 15° C. or higher and 50° C. or lower).

[0090] The heat-absorbing layer (A) can be prepared by mixing the unsaturated polyester, the unsaturated monomer, and the sodium tetraborate hydrate, adding and mixing other additives as necessary, and curing the mixture to obtain the heat-absorbing layer (A) containing the unsaturated polyester resin and the sodium tetraborate hydrate. In particular, a first liquid (first component) containing the unsaturated polyester, the unsaturated monomer, and the sodium tetraborate hydrate, and other additives as necessary, and a second liquid (second component) containing an initiator are prepared, and the first liquid and the second liquid are mixed and reacted to obtain the heat absorbing layer (A). The sodium tetraborate hydrate and other additives may be mixed only with the first component, or may be mixed with the second component as necessary. In such a case, it is particularly preferable to mix and react at a temperature of 10° C. or higher and 70° C. or lower (more preferably 15° C. or higher and 50° C. or lower).

[0091] [Endothermic layer (B)] The heat absorption layer (B) is different from the heat absorption layer (A) in that it does not contain (substantially does not contain) sodium tetraborate hydrate, specifically, it is a heat absorption layer that does not contain (substantially does not contain) the organic binder (urethane resin, polyol and isocyanate constituting the urethane resin, unsaturated polyester resin, unsaturated polyester and unsaturated monomer constituting the unsaturated polyester resin) or sodium tetraborate hydrate (including sodium tetraborate decahydrate). Note that "substantially does not contain" refers to less than 5% by mass of the entire heat absorption layer (B).

[0092] (Inorganic binder) Examples of the inorganic binder include hydraulic inorganic binders, and among them, hydraulic inorganic binders are preferred from the viewpoint of heat absorption.

[0093] Examples of the hydraulic inorganic binder include portland cement, alumina cement, ultra rapid hardening cement, expansion cement, acidic phosphate cement, silica cement, lime mixed cement, blast furnace cement, fly ash cement, Keene's cement, magnesia cement, dolomite, calcium silicate, hydraulic lime, gypsum, etc., and one or more of these can be used.

[0094] The hydraulic inorganic binder can form a large amount of bound water when binding, and can contain a large amount of bound water in the heat absorbing layer (B). As a result, when the temperature rises, it can exhibit excellent heat absorbing properties by utilizing the latent heat of vaporization of the bound water. Furthermore, the heat absorbing layer (B) containing the hydraulic inorganic binder has excellent strength, and can make the strength of the laminate of the present invention excellent.

[0095] The heat absorbing layer (B) may contain other additives in addition to the inorganic binder. Examples of the other additives include water, fillers, water reducing agents, setting regulators, flame retardants, metal hydrates, fibers, adhesion improvers, water repellents, dispersants, surfactants, defoamers, and rust inhibitors. The organic binder may also be contained to the extent that it does not impair the effects of the present invention.

[0096] The heat-absorbing layer (B) can be obtained by mixing the inorganic binder and, if necessary, other additives, and hardening the mixture. For example, the heat-absorbing layer (B) can be obtained by mixing the inorganic binder and other additives with water, forming a kneaded mixture (slurry), and curing and hardening the mixture to obtain the heat-absorbing layer (B). In addition, during production, reinforcing materials such as glass nonwoven fabric, glass cloth, and ceramic paper can also be embedded.

[0097] Examples of such a heat absorption layer (B) include cement board, reinforced cement board, glass fiber mixed cement board, calcium silicate board, glass fiber mixed calcium silicate board, gypsum board (GB-R), ordinary hard gypsum board (GB-RH), non-combustible laminated gypsum board (gypsum board using non-combustible base paper as a cover) (GB-NC), reinforced gypsum board (gypsum board having a core material of gypsum mixed with inorganic fibers such as glass fiber) (GB-F), structural gypsum board (gypsum board having improved lateral nail resistance compared to reinforced gypsum board) (GB-St-A·B), glass fiber nonwoven fabric-containing gypsum board (gypsum board having a core material of gypsum mixed with glass fiber and having glass fiber nonwoven fabric inserted on the front and back sides).

[0098] [Laminate] The laminate of the present invention may be a laminate of at least two heat absorbing layers including a heat absorbing layer (A) formed of a binder and sodium tetraborate hydrate.

[0099] The lamination method is not particularly limited, and the laminate can be produced by a method (1) in which the heat absorption layer (A) and the heat absorption layer (B) are prepared in advance and then laminated using an adhesive or the like; a method (2) in which the components constituting the heat absorption layer (A) are poured so that they come into contact with the heat absorption layer (A) or heat absorption layer (B) prepared in advance, and then hardened to form the heat absorption layer (A); a method (3) in which the components constituting the heat absorption layer (B) are poured so that they come into contact with the heat absorption layer (A) prepared in advance, and then hardened to form the heat absorption layer (B); or a method that combines these methods.

[0100] The methods (2) and (3) allow for adhesive-free lamination (direct lamination without using adhesive), and can suppress heat generation caused by the adhesive when exposed to high temperatures due to a fire, etc. For example, the method (2) has excellent adhesion.

[0101] Specific examples of the laminate of the present invention include laminates having, from the heating surface side, heat absorption layer (A) / heat absorption layer (A), heat absorption layer (A) / heat absorption layer (B), and heat absorption layer (B) / heat absorption layer (A).

[0102] Furthermore, the heat absorption layer (A) may include a plurality of heat absorption layers (A) such as heat absorption layer (A1), heat absorption layer (A2), etc., which contain different raw materials other than the binder and sodium tetraborate hydrate or have different thicknesses. The heat absorption layer (B) may include a plurality of heat absorption layers (B) such as heat absorption layer (B1), heat absorption layer (B2), etc., which contain different raw materials other than the inorganic binder or have different thicknesses. For example, when the heat absorption layer is composed of three layers, the laminate may be, from the heating surface side, heat absorption layer (A1) / heat absorption layer (A2) / heat absorption layer (A3), heat absorption layer (A1) / heat absorption layer (A2) / heat absorption layer (B1), heat absorption layer (A1) / heat absorption layer (B1) / heat absorption layer (A2), heat absorption layer (B1) / heat absorption layer (A1) / heat absorption layer (A2), heat absorption layer (A1) / heat absorption layer (B1) / heat absorption layer (B2), heat absorption layer (B1) / heat absorption layer (A1) / heat absorption layer (B2), heat absorption layer (B1) / heat absorption layer (A1) / heat absorption layer (B2), heat absorption layer (B1) / heat absorption layer (B2) / heat absorption layer (A1). Also, the heat absorption layer may be composed of four or more layers.

[0103] The density of the heat absorbing layer (A) is 0.05 g / cm 3 More than 1.5g / cm 3 Less than (more preferably 0.08 g / cm 3 More than 1.2g / cm 3 Less than 0.1 g / cm, more preferably 0.1 g / cm 3 More than 1.0g / cm 3 It is preferable that The density of the heat absorbing layer (B) is 0.1 g / cm 3 More than 1.5g / cm 3 or less (more preferably 0.3 g / cm3 More than 1.2g / cm 3 More preferably, 0.5 g / cm 3 More than 1.0g / cm 3 It is preferable that When the heat absorption layer (heat absorption layer (A) or heat absorption layer (B)) has such a density, it is possible to obtain a heat absorption layer that is lightweight yet excellent in heat resistance, strength, and dimensional stability.

[0104] In addition to the heat absorption layer (A), when the heat absorption layer (B) is included, the density of the entire heat absorption layer is 0.05 g / cm 3 More than 1.5g / cm 3 Less than (more preferably 0.08 g / cm 3 More than 1.2g / cm 3 Less than 0.1 g / cm, more preferably 0.1 g / cm 3 More than 1.0g / cm 3 It is preferable that

[0105] The upper limit of the thickness of the heat-absorbing layer (A) is preferably 50 mm or less, more preferably 40 mm or less, even more preferably 30 mm or less, and most preferably 20 mm or less, and the lower limit is preferably 3 mm or more, more preferably 4 mm or more, even more preferably 5 mm or more, and most preferably 6 mm or more. The thickness of the heat-absorbing layer (A) refers to the total thickness of the heat-absorbing layers (A) even when the heat-absorbing layer (A) has two layers or three or more layers. The thickness of the heat-absorbing layer (A) alone is preferably 3 mm to 25 mm, more preferably 4 mm to 20 mm. The upper limit of the thickness of the heat-absorbing layer (B) is preferably 50 mm or less, more preferably 40 mm or less, even more preferably 30 mm or less, and most preferably 20 mm or less, and the lower limit is preferably 3 mm or more, more preferably 4 mm or more, even more preferably 5 mm or more, and most preferably 6 mm or more. The thickness of the heat-absorbing layer (B) refers to the total thickness of the heat-absorbing layers (B) even when two or more heat-absorbing layers (B) are present. The thickness of the heat-absorbing layer (B) alone is preferably 3 mm to 25 mm, more preferably 4 mm to 20 mm.

[0106] (Other layers) The laminate of the present invention may be laminated with layers other than those described above as necessary, as long as the effects of the present invention are not significantly impaired. Examples of such layers include an adhesive layer, a decorative layer, a heat reflective layer, a reinforcing material layer, and other layers (e.g., a heat shielding layer, a waterproof layer, a water repellent layer, a water shielding layer, a heat insulating material layer, etc.).

[0107] Among these, the adhesive layer is formed by an adhesive used when bonding the layers together, etc. The adhesive used in the adhesive layer may be a known adhesive, such as an aqueous dispersion type, water-soluble type, or solvent-based adhesive whose main raw material is, for example, an acrylic resin, a silicon resin, an epoxy resin, a vinyl resin, a phenolic resin, a polyester resin, a urethane resin, or paraffin.

[0108] As the decorative layer, for example, woodblocks, particle boards, fiberboards, various coating materials, sheet materials, film materials, etc. can be used. These can have various appearances such as transparent or opaque, colorless or colored, non-glossy or glossy, monochromatic or multicolored, flat or uneven, etc. In the present invention, the provision of the decorative layer is useful because it can improve the aesthetics, water resistance, weather resistance, etc. of the laminate of the present invention.

[0109] The heat reflective layer may be a highly heat reflective metal plate, sheet, tape, etc. Specific examples of the heat reflective layer include aluminum foil, aluminum tape, aluminum cloth, aluminum foil / glass nonwoven fabric laminated sheet, aluminum foil / mesh laminated sheet, aluminum foil / synthetic resin laminated sheet, etc.

[0110] The thickness of the heat reflective layer may be appropriately set depending on the application, etc., but from the standpoint of fire resistance, lightweight, etc., it is preferably 0.01 to 1 mm, more preferably 0.02 to 0.8 mm, and even more preferably 0.03 to 0.6 mm.

[0111] The reinforcing material layer may be, for example, a nonwoven fabric, a woven fabric, or a woven material, and one or more of these may be used in combination. Nonwoven fabrics are fabrics (sheets) made of independent fibers (formed without weaving), such as fabrics with crossed fiber arrangements, random fiber arrangements, etc. Furthermore, methods for bonding fibers include chemical adhesion using a resin component (chemical bonding), fusion by heating (thermal bonding), mechanical intertwining (needle punching), stitching (stitch bonding), etc. Examples of woven fabrics include those in which fibers aligned in one direction and fibers aligned in a different direction are woven vertically, horizontally, or diagonally and laminated together. The woven fabric may have a mesh structure, and examples of such woven fabrics include multi-axial woven fabrics such as biaxial woven fabrics, triaxial woven fabrics, and quadraxial woven fabrics, depending on the number of axes of the fiber groups. Woven fabrics are formed from fibers in the same way as woven cloth, and are woven by interlacing warp and weft fibers above and below. Examples of woven fabric structures include plain weave, twill weave, satin weave, double warp weave, double weft weave, double warp and weft weave, pile weave, leno weave, and figured weave.

[0112] Examples of fibers used in the reinforcing layer include inorganic fibers such as rock wool, glass fibers, silica fibers, silica-alumina fibers, carbon fibers, silicon carbide fibers, and the like; fine metal wires such as iron and copper; and organic fibers such as pulp fibers, polyester fibers, polypropylene fibers, aramid fibers, vinylon fibers, polyethylene fibers, polyarylate fibers, PBO fibers, nylon fibers, acrylic fibers, vinyl chloride fibers, and cellulose fibers. One or more of these may be used.

[0113] In the present invention, it is particularly preferable to use a nonwoven fabric in which fibers are randomly arranged as the reinforcing material layer, and it is particularly preferable to use an inorganic fiber nonwoven fabric in which inorganic fibers are randomly arranged and bonded between the inorganic fibers with a resin component. Furthermore, it is preferable to use glass fibers as the inorganic fibers. Such a reinforcing layer can reinforce the strength of the heat absorbing board, as well as the fire resistance and formability.

[0114] The thickness of the reinforcing material layer is preferably about 0.1 to 2 mm, and more preferably about 0.15 to 1 mm.

[0115] When laminating the reinforcing layer and the heat absorbing layer, they can be bonded together using the adhesive layer, or the reinforcing layer can be embedded in the heat absorbing layer, or can be laminated on one or both sides of the heat absorbing layer. For example, in the method of embedding the reinforcing material layer in the heat absorption layer (A), when the mixed liquid of the first liquid and the second liquid is reacted to obtain the heat absorption layer (A), the reinforcing material layer can be embedded in the mixed liquid before the reaction and hardening, and then hardened. Specifically, the method includes pouring an endothermic composition containing a binder and sodium tetraborate hydrate onto a reinforcing material layer and curing the composition; A method of spraying sodium tetraborate hydrate on a reinforcing material layer, pouring a composition containing a binder, and hardening the composition; A method of pouring a composition containing a binder onto a reinforcing material layer, further spraying sodium tetraborate hydrate thereon, and then hardening the composition; Also, after pouring or spraying the endothermic composition, a reinforcing layer can be laminated on the endothermic composition before the endothermic composition hardens. Furthermore, the endothermic composition can be poured and hardened. The degree of embedding is not particularly limited, but may be a fully embedded state in which the reinforcing material layer is entirely embedded, or a semi-embedded state in which only a portion of the reinforcing material layer is exposed to the surface. In the present invention, the strength and fire resistance of the heat absorbing layer (A) can be further improved by using a reinforcing layer that is permeable to the binder but not to the sodium tetraborate hydrate. 2 , and even 20 to 300 g / m 2 It is preferable that:

[0116] (Laminate properties) The laminate of the present invention can be made thinner than those of the conventional technology, and the thickness (total thickness) of the laminate is preferably 60 mm or less, more preferably 10 to 58 mm, and even more preferably 15 to 55 mm. When the thickness of the laminate is equal to or less than the upper limit of the above range, the burden on workers and the risk of injury during transportation and construction work can be reduced, and work efficiency can be improved. When the laminate is applied to indoor pillars, beams, floor slabs, walls, etc., it is also possible to expand the indoor space. When the thickness of the laminate is equal to or more than the lower limit of the above range, it is preferable in terms of fire resistance, strength, etc.

[0117] The mass per unit area of ​​the laminate of the present invention is preferably 40 kg / m 2 Less than or equal to 10 to 35 kg / m 2 , and more preferably 15 to 30 kg / m 2 Since the laminate having such characteristics is lightweight, it is possible to reduce the burden on workers and the risk of injury during transportation, construction work, and the like, and to improve work efficiency.

[0118] The laminate of the present invention can be applied, for example, to building components such as roofs, ceilings, walls, and floors, and to vehicle components, and can be used by laminating it with boards or films made of materials such as metal, plastic, mortar, cement, gypsum, wood, paper, and fiber. In the present invention, it is particularly preferable to apply it to wood materials, plastic materials, paper materials, fiber materials, and the like.

[0119] Examples of the wood materials include lumber, plywood, laminated lumber, LVL (Laminated Veneer Lumber), CLT (Cross Laminated Timber), particle board, fiberboard, etc. The use of such wood materials also contributes to the promotion of carbon neutrality.

[0120] Among the wood materials, the CLT is called cross-laminated timber, which is a wood material in which sawn boards (lamina) are arranged and then laminated so that the fiber direction is perpendicular. Specifically, CLT is defined in the Japanese Agricultural Standard JAS3079:2019 "Cross-laminated timber" as "wood in which sawn boards or small square timbers (including those adjusted by joining and gluing them in the length direction with their fiber directions approximately parallel to each other) are arranged or glued in the width direction with their fiber directions approximately parallel to each other, and are mainly laminated and glued with their fiber directions approximately perpendicular to each other to have a structure of three or more layers." By using CLT as a wood substrate, it becomes possible to apply the laminate of the present invention to structural members (structural bodies) and the like.

[0121] The thickness of the wood material can be appropriately set depending on the application, etc.

[0122] The plastic material may be a material containing a thermoplastic resin and / or a thermosetting resin as a main component.

[0123] Examples of the thermoplastic resin include polyamide, polyacetal, polysulfone, polyester, polybutylene terephthalate, polycarbonate, polyethylene terephthalate, polyethylene, polypropylene, polyphenylene sulfide, polyether ether ketone, polyether imide, polyether ketone ketone, polyvinyl chloride, acrylic resin, ABS resin, fluororesin, and silicone resin.

[0124] As the thermosetting resin, those that form a three-dimensional crosslinked structure by a crosslinking reaction can be used, and examples thereof include unsaturated polyester resins, vinyl ester resins, epoxy resins, benzoxazine resins, phenolic resins, urethane resins, urea resins, melamine resins, polyimide resins, etc. These can be used alone or in combination of two or more.

[0125] In the present invention, a fiber-reinforced plastic material can be used as the plastic material. The fiber-reinforced plastic material is a composite of the above-mentioned resin and fiber, and is a material having properties such as high specific rigidity and high specific strength. By using a fiber-reinforced plastic material as the plastic material, it becomes possible to apply the laminate of the present invention to structural members (structural bodies) and the like.

[0126] Examples of the fibers used in the fiber-reinforced plastic material include glass fibers, aramid fibers, Kevlar fibers, carbon fibers, graphite fibers, boron fibers, Tyranno fibers, silicon carbide fibers, silicon nitride fibers, alumina fibers, and mineral fibers, and among these, glass fibers and carbon fibers are preferred from the viewpoint of improving mechanical strength, and glass fibers are also preferred from the viewpoint of cost. These can be used alone or in combination of two or more kinds.

[0127] The thickness of the plastic material can be appropriately set depending on the application, etc.

[0128] Various materials can also be laminated together with the laminate, such as an adhesive layer, a decorative layer, and other layers (e.g., a reinforcing material layer, a heat reflective layer, a heat shielding layer, a waterproof layer, a water repellent layer, a water shielding layer, a heat insulating material layer, etc.). EXAMPLES

[0129] The features of the present invention will be more clearly described below with reference to examples and comparative examples, but the present invention should not be construed as being limited to these examples.

[0130] The following materials were used as materials for constructing the laminate used as a test specimen.

[0131] · Endothermic layer A1 constituents: Endothermic layer A1 first component Unsaturated polyester resin (unsaturated polyester / styrene (mass ratio 60 / 40)) 50 parts by mass Sodium tetraborate decahydrate 100 parts by mass Endothermic layer A1 second component Methyl ethyl peroxide 1 part by mass

[0132] Heat absorption layer B1: Glass fiber nonwoven fabric gypsum board (thickness 8 mm, mass 6.8 kg / m 2 ) Heat absorption layer B2: Reinforced gypsum board (thickness 12.5 mm, mass 10.6 kg / m 2 )

[0133] Reinforcement layer: Nonwoven fabric with randomly arranged glass fibers (thickness 0.4 mm, basis weight 50 g / m 2 )

[0134] [Example 1] (Test piece 1) A mixture of the first and second components of the heat absorption layer A1 was poured into a mold and cured at 40° C. for 1 hour to obtain a heat absorption layer A1 (100 mm×100 mm). Furthermore, the heat absorption layer A1 was laminated on the heat absorption layer B1 (100 mm×100 mm) using a vinyl acetate resin adhesive to obtain a laminate (test piece 1) of the heat absorption layer B1 and the heat absorption layer A1. The content of sodium tetraborate hydrate in the heat absorption layer A1 is 4.2 kg / m 2 It was. The thickness of the heat-absorbing layer A1 is 8 mm, and the weight per unit area is 10.3 kg / m 2 It was. The test piece 1 was placed so that the heat absorbing layer B1 side was the heated side, and the following fire resistance test was carried out. As a result, the evaluation was "A". The test piece 1 was placed so that the heat absorbing layer A1 side was the heated side, and the following fire resistance test was carried out. As a result, the evaluation was "B".

[0135] [Example 2] (Test piece 2) A mixture of the first and second components of the heat absorption layer A1 was poured into a mold (100 mm x 100 mm), reacted at 40°C for 1 hour, and demolded to obtain the heat absorption layer A1. A mixture of the first and second components of the heat absorption layer A1 was poured on top of the mold, reacted at 40°C for 1 hour, and obtained the heat absorption layer A1. The mold was demolded to obtain a laminate (test piece 2) of the heat absorption layer A1 and the heat absorption layer A1. The content of sodium tetraborate hydrate in the heat absorption layer A1 is 8.4 kg / m 2 It was. The thickness of the heat absorption layer A1 (total) is 16 mm, and the weight per unit area is 20.6 kg / m 2 It was. The test piece 2 was placed so that the heat absorbing layer A1 side was the heated side, and the following fire resistance test was carried out. As a result, the evaluation was "A".

[0136] [Example 3] (Test piece 3) A mixture of the first and second components of the heat absorption layer A1 was poured into a mold (100 mm x 100 mm), reacted at 40°C for 1 hour, and demolded to obtain the heat absorption layer A1. Similarly, another heat absorption layer A1 was obtained, and the two heat absorption layers A1 were laminated together using an acrylic adhesive to obtain a laminate (test piece 3) of the heat absorption layer A1 and the heat absorption layer A1. The content of sodium tetraborate hydrate in the heat absorption layer A1 (1 sheet) is 4.2 kg / m 2 It was. The thickness of the heat-absorbing layer A1 (one sheet) is 8 mm, and the weight per unit area is 10.3 kg / m 2 It was. The test piece 3 was placed so that the heat absorbing layer A1 side was the heated side, and the following fire resistance test was carried out. As a result, the evaluation was "A".

[0137] [Example 4] (Test piece 4) The mixture of the first and second components of the heat absorption layer A1 was poured into a mold (100 mm x 100 mm) and cured at 40° C. for 1 hour to obtain a heat absorption layer A1 (100 mm x 100 mm). Another heat absorption layer A1 (100 mm x 100 mm) was obtained in the same manner. Furthermore, the heat absorption layer A1 and the heat absorption layer A1 were laminated in this order on the heat absorption layer B1 (100 mm x 100 mm) using a vinyl acetate resin adhesive to obtain a laminate (test piece 4) of the heat absorption layer B1, the heat absorption layer A1 and the heat absorption layer A1. The content of sodium tetraborate hydrate in the heat absorption layer A1 (1 sheet) is 4.2 kg / m 2 It was. The thickness of the heat-absorbing layer A1 (one sheet) is 8 mm, and the weight per unit area is 10.3 kg / m 2 It was. The test piece 4 was placed so that the heat absorbing layer B1 side was the heated side, and the following fire resistance test was carried out. As a result, the evaluation was "AA". The test piece 4 was placed so that the heat absorbing layer A1 side was the heated side, and the following fire resistance test was carried out. As a result, the evaluation was "AA".

[0138] [Example 5] (Test piece 5) The mixture of the first and second components of the heat absorption layer A1 was poured into a form (100 mm x 100 mm) and cured at 40°C for 1 hour to obtain a heat absorption layer A1 (100 mm x 100 mm). Furthermore, the heat absorption layer A1 was laminated on the heat absorption layer B2 (100 mm×100 mm) using a vinyl acetate resin adhesive to obtain a laminate (test piece 5) of the heat absorption layer B2 and the heat absorption layer A1. The content of sodium tetraborate hydrate in the heat absorption layer A1 is 4.2 kg / m 2 It was. The thickness of the heat-absorbing layer A1 is 8 mm, and the weight per unit area is 10.3 kg / m 2 It was. The test piece 5 was placed so that the heat absorbing layer B2 side was the heated surface side, and the following fire resistance test was carried out. As a result, the evaluation was "A". The test piece 5 was placed so that the heat absorbing layer A1 side was the heated side, and the following fire resistance test was carried out. As a result, the evaluation was "A".

[0139] [Example 6] (Test piece 6) A reinforcing material layer was laid on a formwork (100 mm x 100 mm), and a mixed liquid of the first constituent component of the heat absorption layer A1 and the second constituent component of the heat absorption layer A1 was poured on top of it, and allowed to react and harden at 40°C for 1 hour to obtain a laminate (100 mm x 100 mm) of the reinforcing material layer and the heat absorption layer A1. Furthermore, the laminate was laminated on top of the heat absorption layer B2 (100 mm x 100 mm) using a vinyl acetate resin adhesive so that the reinforcing layer side was adhered to the laminate, thereby obtaining a laminate (test piece 6) of the heat absorption layer B2, the reinforcing layer and the heat absorption layer A1. The content of sodium tetraborate hydrate in the heat absorption layer A1 is 4.2 kg / m 2 It was. The thickness of the heat-absorbing layer A1 is 8 mm, and the weight per unit area is 10.3 kg / m 2 It was. The test piece 6 was placed so that the heat absorbing layer B2 side was the heated side, and the following fire resistance test was carried out. As a result, the evaluation was "AA". The test piece 6 was placed so that the heat absorbing layer A1 side was the heated side, and the following fire resistance test was carried out. As a result, the evaluation was "A".

[0140] [Example 7] (Test piece 7) A reinforcing layer was laid on a formwork (100mm x 100mm), and a mixed liquid of the first component of the heat absorption layer A1 and the second component of the heat absorption layer A1 was poured on top of it, and reacted and cured at 40°C for 1 hour to obtain a laminate (100mm x 100mm) of the reinforcing layer and the heat absorption layer A1. Another laminate (100mm x 100mm) of the reinforcing layer and the heat absorption layer A1 was obtained in the same manner. Furthermore, a laminate was laminated on top of the heat absorption layer B2 (100 mm x 100 mm) using a vinyl acetate resin adhesive so that the reinforcing material layer side was adhered, and then a laminate was laminated further so that the reinforcing material layer side was adhered, obtaining a laminate (test piece 7) of the heat absorption layer B2, the reinforcing material layer, the heat absorption layer A1, the reinforcing material layer and the heat absorption layer A1. The content of sodium tetraborate hydrate in the heat absorption layer A1 is 8.4 kg / m 2 It was. The total thickness of the heat absorbing layer A1 is 16 mm, and the weight per unit area is 20.6 kg / m 2 It was. The test piece 7 was placed so that the heat absorbing layer B2 side was the heated side, and the following fire resistance test was carried out. As a result, the evaluation was "AA". The test piece 7 was placed so that the heat absorbing layer A1 side was the heated side, and the following fire resistance test was carried out. As a result, the evaluation was "AA".

[0141] [Example 8] (Test piece 8) A mixture of the first and second components of the heat absorption layer A1 was poured into a formwork (100 mm x 100 mm) and reacted and cured at 40°C for 1 hour to obtain a heat absorption layer A1 (100 mm x 100 mm). Furthermore, a heat absorption layer A1 was laminated on top of the heat absorption layer B2 (100 mm x 100 mm) using a vinyl acetate resin adhesive, and then a heat absorption layer B1 (100 mm x 100 mm) was laminated on top of that to obtain a laminate (test piece 8) of the heat absorption layer B2, the heat absorption layer A1 and the heat absorption layer B1. The content of sodium tetraborate hydrate in the heat absorption layer A1 is 4.2 kg / m 2 It was. The thickness of the heat-absorbing layer A1 is 8 mm, and the weight per unit area is 10.3 kg / m 2 It was. The test piece 8 was placed so that the heat absorbing layer B2 side was the heated surface side, and the following fire resistance test was carried out. As a result, the evaluation was "AA". The test piece 8 was placed so that the heat absorbing layer B1 side was the heated surface side, and the following fire resistance test was carried out. As a result, the evaluation was "AA".

[0142] [Example 9] (Test piece 9) A mixture of the first component of the heat absorption layer A1 and the second component of the heat absorption layer A1 was poured into a mold (100 mm x 100 mm) and cured at 40°C for 1 hour to obtain a heat absorption layer A1 (100 mm x 100 mm). Another heat absorption layer A1 (100 mm x 100 mm) was obtained in the same manner. Furthermore, the heat absorption layer A1 was laminated on both sides of the heat absorption layer B2 (100 mm×100 mm) using a vinyl acetate resin adhesive to obtain a laminate (test piece 9) of the heat absorption layer A1, the heat absorption layer B2 and the heat absorption layer A1. The content of sodium tetraborate hydrate in the heat absorption layer A1 (1 sheet) is 4.2 kg / m 2 It was. The thickness of the heat-absorbing layer A1 (one sheet) is 8 mm, and the weight per unit area is 10.3 kg / m 2 It was. The test piece 9 was placed so that the heat absorbing layer A1 side was the heated side, and the following fire resistance test was carried out. As a result, the evaluation was "AA".

[0143] [Comparative Example 1] The heat absorption layer B1 was placed in a formwork (100 mm x 100 mm), and another heat absorption layer B1 was laminated on top of the heat absorption layer B1 using an acrylic adhesive to obtain a laminate (test piece 10) of the heat absorption layer B1 and the heat absorption layer B1. The test specimen 10 was placed so that the heat absorbing layer B1 side was the heated side, and the following fire resistance test was carried out. As a result, the evaluation was "D".

[0144] [Comparative Example 2] A mixture of 50 parts by mass of unsaturated polyester resin (unsaturated polyester / styrene (mass ratio 60 / 40)) and 1 part by mass of methyl ethyl peroxide was poured into a formwork (100 mm x 100 mm) and allowed to react and harden at 40°C for 1 hour to obtain a polyester resin layer (100 mm x 100 mm). Furthermore, a polyester resin layer was laminated on the heat absorbing layer B1 (100 mm×100 mm) using a vinyl acetate resin adhesive to obtain a laminate (specimen 11) of the heat absorbing layer B1 and the polyester resin layer. The test piece 11 was placed so that the heat absorbing layer B1 side was the heated side, and the following fire resistance test was carried out. As a result, the evaluation was "D".

[0145] (Fire resistance test) Each of the test specimens 1 to 11 (laminates) was subjected to a fire resistance test using a cone calorimeter specified in ISO 5660. The heating intensity was 50 kW / m 2 The heating time was 90 minutes. In the fire resistance test, the temperature of the back side of the test specimen was measured during heating, and the fire resistance was evaluated based on the maximum temperature reached. The back side of the test specimen here refers to the side that was not heated. The evaluation criteria are as follows: Note that, as a practical level, the evaluation criteria of AA, A, or B are preferable. (Evaluation Criteria) AA: Maximum temperature is 125℃ or less A: The maximum temperature is over 125℃ and below 150℃ B: Maximum temperature is over 150℃ and below 200℃ C: Maximum temperature is over 200℃ and below 250℃ D: Maximum temperature exceeds 250℃

Claims

1. A laminate including a first heat absorption layer and a second heat absorption layer, A laminate, characterized in that the first heat absorption layer and / or the second heat absorption layer are formed from a binder and sodium tetraborate hydrate.

2. A laminate including a first heat absorption layer and a second heat absorption layer, A laminate, wherein the first heat absorption layer and the second heat absorption layer are formed from a binder and sodium tetraborate hydrate.

3. A laminate including a first heat absorption layer and a second heat absorption layer, the first heat absorption layer is formed of a binder and sodium tetraborate hydrate; The laminate, wherein the second heat absorption layer is formed from an inorganic binder and is substantially free of sodium tetraborate hydrate.

4. The laminate according to any one of claims 1 to 3, wherein the sodium tetraborate hydrate comprises sodium tetraborate decahydrate.

5. The laminate according to claim 1 , wherein the binder comprises an organic binder.

6. 6. A laminate according to claim 5, wherein the organic binder is obtained from an unsaturated polyester and an unsaturated monomer.

7. 4. The laminate according to claim 1, wherein the first heat absorption layer and the second heat absorption layer each have a thickness of 50 mm or less.

Citation Information

Patent Citations

  • Non-combustible improved gypsum board

    JP1997302804A